Effect of prone positioning in adult patients receiving veno-venous extracorporeal membrane oxygenation: A meta-analysis - Dehua Zeng; Aiqun Zhu; Jiayi Zhao (PLoS ONE, 2025)
Objective To investigate the effects of prone positioning during extracorporeal membrane oxygenation (ECMO) and its effects on short-term and long-term survival. Methods A computerized search was performed for all studies in PubMed, Web of Science, Embase, and the Cochrane Library up to December 31, 2023, including prospective and retrospective clinical studies of ECMO-treated patients with or without prone positioning. Titles, abstracts, and full-text articles were screened in duplicate by two investigators. The primary outcome was short‐term survival (survival at discharge or 1-month survival). The secondary outcomes included long-term survival (60-day survival, 90-day survival), ECMO duration, length of intensive care unit (ICU) stay and ECMO weaning. Results Fifteen studies with 2608 patients were included, most of which were retrospective. The effect of prone versus non-prone positioning in ECMO patients was OR =  1.32; 95% CI, 0.88–1.97; P =  0.18 for short-term survival from the original data. The effects of prone positioning during ECMO were a significant increase in 28-day survival (OR = 2.54; 95% CI 1.71–3.76; P < 0.00001) and survival at discharge (OR = 1.49; 95% CI 1.11–2.00; P = 0.009), which appeared in the non-COVID-19 patient group. Furthermore, the short-term effects of prone ventilation in ECMO patients were also improved in the matching analysis (OR = 1.66; 95% CI, 1.23–2.23; P = 0.0008), but did not in the long-term survival rate (OR = 1.57; 95% CI, 0.90–2.76; P = 0.11). The durations of ECMO (OR = 1.99; 95% CI, 1.99–2.70; P < 0.00001) and ICU stay (OR = 1.17; 95% CI, 0.58–1.75; P < 0.0001) were significantly different between the prone group and the non-prone group. Conclusion Prone position ventilation during ECMO confers no significant advantage in improving long-term survival and only slightly benefits short-term survival. Therefore, the prone position during ECMO should be carefully considered because further randomized clinical trials on this subject are needed.